Endophytic fungi associated with leaves and roots of Zhizophora x lamarkii. - Manipol, Ryel Katherine V.
Studies on fungal endophytes among various species of true mangroves has been reported from countries outside of the Philippines undertaken for diversity studies and the search for new compounds with biotechnological applications. However, in the Philippines, there has been very minimal studies done when the country is a host to many species of true mangroves and many more species are waiting for investigations. Thus, this study was conducted to isolate and identify endophytic fungi associated with leaves and roots of Rhizophora x lamarckii, a mangrove hybrid in Taklong Island National Marine Reserve, Nueva Valencia, Guimaras. Specifically, it aimed to 1) describe population of fungal endophytes in terms of: a) overall species composition and frequency of occurrence, b). species composition and frequency of occurrence according to sample type, c). total frequency of occurrence according to sample type, d). Shannon Index of Diversity and Evenness, and e). compare Jaccard's index of similarity of fungal population among sample types. Samples of leaves and roots Rhizophora x lamarckii were collected from the field and processed within 24 hrs in the laboratory. Sterilized leaf discs and root segments were inoculated on Potato Dextrose Agar (PDA) with streptomycin. Plates were inocubated at 25 +- 2 degrees centigrade for 2-3 weeks and examined on a daily basis for fungal growth. Identification of isolates was based on available keys and monographs. A total of sixteen (16) species were collected from 30 samples of roots and leaves. In general, Nodulisporium sp (21.3 percent) and Aspergillus sp. (20 percent) were the very frequently collected species. The frequently occurring species included Aspergillus sp. 2, Paecilomyces sp. 1, Penicillium sp. 1, Taeniolella sp., Aspergillus sp. 3 Asteromyces sp. The overall Shannon Index of Diversity was 1.35 and Dominance Index at 0.89. More species were collected from leaves than roots at 14 and 6 respectively. However, similarity of species composition was only 25 percent with ten species occuring exclusively in leaves and two roots while four species were collected from both tissue types. Results possibly indicate tissue specificity or preference. This is the first report on the occurrence of fungal endophytes in the mangrove hybrid, Rhizophora x lamarckii.